2007
DOI: 10.1038/nmeth1062
|View full text |Cite
|
Sign up to set email alerts
|

Bright monomeric red fluorescent protein with an extended fluorescence lifetime

Abstract: Fluorescent proteins have become extremely popular tools for in vivo imaging and especially for the study of localization, motility and interaction of proteins in living cells. Here we report TagRFP, a monomeric red fluorescent protein, which is characterized by high brightness, complete chromophore maturation, prolonged fluorescence lifetime and high pH-stability. These properties make TagRFP an excellent tag for protein localization studies and fluorescence resonance energy transfer (FRET) applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
505
1
4

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 590 publications
(533 citation statements)
references
References 16 publications
11
505
1
4
Order By: Relevance
“…A survey of Sun2 immunoreactivity in cells containing LULL1-redistributed TorA-mGFP indicated that changes in Sun2 were widespread; 60% of these cells lacked a clearly delineated nuclear rim of Sun2 compared with only 4% of untransfected cells (n Ͼ 110 for each). To rule out the alternative possibility that redistributed TorA masked the lumenal Sun2 antibody epitope (Hodzic et al, 2004), we made a tetracycline-inducible LULL1-myc cell line that also constitutively expressed Sun2-GFP and assessed the effect of introducing TorA fused to TagRFP (Merzlyak et al, 2007). Direct examination of protein fluorescence showed that Sun2-GFP was displaced by TorA-TagRFP ( Figure 6D), paralleling the effect of TorA on endogenous Sun2.…”
Section: Redistributed Tora Displaces a Subset Of Linc Complexmentioning
confidence: 99%
See 1 more Smart Citation
“…A survey of Sun2 immunoreactivity in cells containing LULL1-redistributed TorA-mGFP indicated that changes in Sun2 were widespread; 60% of these cells lacked a clearly delineated nuclear rim of Sun2 compared with only 4% of untransfected cells (n Ͼ 110 for each). To rule out the alternative possibility that redistributed TorA masked the lumenal Sun2 antibody epitope (Hodzic et al, 2004), we made a tetracycline-inducible LULL1-myc cell line that also constitutively expressed Sun2-GFP and assessed the effect of introducing TorA fused to TagRFP (Merzlyak et al, 2007). Direct examination of protein fluorescence showed that Sun2-GFP was displaced by TorA-TagRFP ( Figure 6D), paralleling the effect of TorA on endogenous Sun2.…”
Section: Redistributed Tora Displaces a Subset Of Linc Complexmentioning
confidence: 99%
“…TorA-TagRFP was made by transferring TorA mutants excised with XhoI and EcoRI from EGFP-N1 into a RFP-N1 vector containing TagRFP (Merzlyak et al, 2007). The TorA ⌬26-43 deletion was created by QuikChange mutagenesis (Stratagene, La Jolla, CA).…”
Section: Plasmidsmentioning
confidence: 99%
“…3 and Supplementary movies [1][2][3][4][5][6][7][8]. Owing to the lack of a statistical methodology to make direct comparisons of fluorescent protein performance in fusions, the practice is utilized only to provide one or several representative images that demonstrate the ability of the reporter to properly perform in each of the constructs.…”
Section: Performance Of Fusionred In Fusionsmentioning
confidence: 99%
“…Over the past decade, a number of red dimeric and tetrameric fluorescent proteins have been subjected to artificial monomerization, which in most cases has resulted in a loss of brightness, a slower maturation rate and reduced fluorescence stability. Engineered red monomers, such as mCherry and other mFruit proteins 3 , along with mKO 4 , TagRFP 5 and mKate2 (refs 6,7) are suitable fusion partners for many proteins of interest. However, these proteins usually do not perform as well as Aequorea victoria GFP derivatives in fusions, and often present issues related to abnormal subcellular protein localization, aggregation, or toxic effects 8 .…”
mentioning
confidence: 99%
“…At this time, we recommend superfolder GFP [56, 57], secBFP2 [47], and FusionRed [58] for protein fusions. For transcriptional reporters, mNeonGreen matures rapidly and produces an intense signal [59] and TagRFP has similar properties for a red reporter [60]. …”
Section: Approaches For Imaging Er Stress and Upr Activity In Livinmentioning
confidence: 99%